APLIKASI MODEL PEMBELAJARAN KOOPERATIF TERHADAP PENINGKATAN KUALITAS BELAJAR PADA MATA PELAJARAN BAHASA INDONESIA - Erlinawati, Mira; Dyah Rupa Murti, Arini (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2025)
This study aims to see how far the implementation of the cooperative learning model has improved the quality of learning in the Indonesian language subject. The researcher collaborated with Indonesian language teachers at the junior high school level in Brebes Regency as a research sample. The research method used is qualitative with a literature study approach. Primary data was obtained from in-depth interviews with research subjects. Secondary data was obtained from the results of the analysis of literature sources. The results of this study state that the cooperative learning model gradually has a good impact on learning activities, students' absorption of materials and learning completeness. Increased learning activities, student absorption and learning completeness can be said to be progress and positive results on the quality of student learning, so the author concludes that the cooperative learning model can be said to have a good influence on the quality of student learning. Learning activities are at 73.2%. While in cycle II the figure jumped to 89%. The spike in student learning activities is a natural thing considering that in its development students have a limited view of something new, but this view will be different if something is already known and explored.